The ACCENT-VOCBAS field campaign on biosphere-atmosphere interactions in a Mediterranean ecosystem of Castelporziano (Rome): site characteristics, climatic and meteorological conditions, and eco-physiology of vegetation - Fares, S; Mereu, S; Scarascia Mugnozza, G; Vitale, M; Manes, F; Frattoni, M; Ciccioli, P; Gerosa, G; Loreto, F (Biogeosciences, 2009)
Biosphere-atmosphere interactions were investigated on a sandy dune Mediterranean ecosystem in a ﬁeld campaign held in 2007 within the frame of the European Projects ACCENT and VOCBAS. The campaign was carried out in the Presidential estate of Castelporziano, a periurban park close to Rome. Former campaigns (e.g. BEMA) performed in Castelporziano investigated the emission of biogenic volatile organic compounds (BVOC). These campaigns focused on pseudosteppe and evergreen oak groves whereas the contribution of the largely biodiverse dune vegetation, a prominent component of the Mediterranean ecosystem, was overlooked. While speciﬁc aspects of the campaign will be discussed in companion papers, the general climatic and physiological aspects are presented here, together with information regarding BVOC emission from the most common plant species of the dune ecosystem. During the campaign regular air movements were observed, dominated by moderate nocturnal land breeze and diurnal sea breeze. A regular daily increase of ozone concentration in the air was also observed, but daily peaks of ozone were lower than those measured in summer on the same site. The site was ideal as a natural photochemical reactor to observe reaction, transport and deposition processes occurring in the Mediterranean basin, since the sea-land breeze circulation allowed a strong mixing between biogenic and anthropogenic emissions and secondary pollutants. Measurements were run in May, when plant physiological conditions were optimal, in absence of severe drought and heat stress. Foliar rates of photosynthesis and transpiration were as high as generally recorded in unstressed Mediterranean sclerophyllous plants. Most of the plant species emitted high level of monoterpenes, despite measurements being made in a period in which emissions of volatile isoprenoids could be restrained by developmental and environmental factors, such as leaf age and relatively low air temperature. Emission of isoprene was generally low. Accounting for the high monoterpene spring emission of the dune ecosystem may be important to correct algorithms at regional and ecosystem levels, and to interpret measurements of ﬂuxes of volatile isoprenoids and secondary pollutants.
Keywords: BVOC emission; Castelporziano; Mediterranean ecosystem; stress (voyant); Water availability

Concentrations and fluxes of biogenic volatile organic compounds above a Mediterranean macchia ecosystem in western Italy - Davison, B; Taipale, R; Langford, B; Misztal, P; Fares, S; Matteucci, G; Loreto, F; Cape, J N; Rinne, J; Hewitt, C N (BIOGEOSCIENCES, 2009)
Emission rates and concentrations of biogenic volatile organic compounds (BVOCs) were measured at a Mediterranean coastal site at Castelporziano, approximately 25 km south-west of Rome, between 7 May and 3 June 2007, as part of the ACCENT-VOCBAS field campaign on biosphere-atmosphere interactions. Concentrations and emission rates were measured using the disjunct eddy covariance (DEC) method utilizing three different proton transfer reaction mass spectrometers (PTR-MS) so allowing a comparison between the instruments. The high resolution data from the PTR-MS instruments considerably enhances the original BEMA measurements of the mid 1990s. Depending on the measurement period, the volume mixing ratios were in the range 1.6-3.5 ppbv for methanol, 0.44-1.3 ppbv for acetaldehyde, 0.96-2.1 ppbv for acetone, 0.10-0.14 ppbv for isoprene, and 0.13-0.30 ppbv for monoterpenes. A diurnal cycle in mixing ratios was apparent with daytime maxima for methanol, acetaldehyde, acetone, and isoprene. The fluxes ranged from 370-440 mu g m(-2) h(-1) for methanol, 180-360 mu g m(-2) h(-1) for acetaldehyde, 180-450 mu g m(-2) h(-1) for acetone, 71-290 mu g m(-2) h(-1) for isoprene, and 240-860 mu g m(-2) h(-1) for monoterpenes. From the measured flux data (7 May-3 June) an average basal emission rate for the Macchia vegetation was calculated of 430 mu g m(-2) h(-1) for isoprene and 1100 mu g m(-2) h(-1) for monoterpenes.
APS
Keywords: BVOCS; Emission rates; Mediterranean; Monoterpenes

Stomatal uptake and stomatal deposition of ozone in isoprene and monoterpene emitting plants - Fares, S; Loreto, F; Kleist, E; Wildt, J (Plant Biology, 2008)
Volatile isoprenoids were reported to protect plants against ozone. To understand whether this could be the result of a direct scavenging of ozone by these molecules, the stomatal and non-stomatal uptake of ozone was estimated in plants emitting isoprene or monoterpenes. Ozone uptake by holm oak (Quercus ilex, a monoterpene emitter) and black poplar (Populus nigra, an isoprene emitter) was studied in whole plant enclosures (continuously stirred tank reactors, CSTR). The ozone uptake by plants was estimated measuring ozone concentration at the inlet and outlet of the reactors, after correcting for the uptake of the enclosure materials. Destruction of ozone at the cuticle or at the plant stems was found to be negligible compared to the ozone uptake through the stomata. For both plant species, a relationship between stomatal conductance and ozone uptake was found. For the poplar, the measured ozone losses were explained by the uptake of ozone through the stomata only, and ozone destruction by gas phase reactions with isoprene was negligible. For the oak, gas phase reactions of ozone with the monoterpenes emitted by the plants contributed significantly to ozone destruction. This was confirmed by two different experiments showing a) that in cases of high stomatal conductance but under low CO2 concentration, a reduction of monoterpene emission was still associated with reduced O3 uptake; and b) that ozone losses due to the gas phase reactions only can be measured when using the exhaust from a plant chamber to determine the gas phase reactivity in an empty reaction chamber. Monoterpenes can therefore relevantly scavenge ozone at leaf level contributing to protection against ozone.
Keywords: isoprene; Monoterpenes; Ozone uptake; photosynthesis; reaction chambers; Stomatal conductance

On the monoterpene emission under heat stress and on the increased thermotolerance of leaves of Quercus ilex L. fumigated with selected monoterpenes - Loreto, F; Förster, A; Dürr, M; Csiky, O; Seufert, G (Plant, Cell & Environment, 1998)
Leaves of the monoterpene emitter Quercus ilex were exposed to a temperature ramp with 5 °C steps from 30 to 55 °C while maintained under conditions in which endogenous emission of monoterpenes was allowed or suppressed, or under fumigation with selected exogenous monoterpenes. Fumigation with monoterpenes reduced the decline of photosynthesis, photorespiration and monoterpene emission found in non-fumigated leaves exposed to high temperatures. It also substantially increased respiration when photosynthesis and photorespiration were inhibited by low O2 and CO2-free air. These results indicate that, as previously reported for isoprene, monoterpenes may help plants cope with heat stress. Monoterpenes may enhance membrane stability, thus providing a rather non-specific protection of photosynthetic and respiratory processes. Monoterpene emission was maximal at a temperature of 35 °C and was inhibited at higher temperatures. This is likely to be the result of the temperature dependency of the enzymes involved in monoterpene synthesis. In contrast to other monoterpenes, cis- and trans-β-ocimene did not respond to exposure to high temperatures. Cis-β-ocimene also did not respond to low O2 or to fumigation. These results indicate that cis and trans-β-ocimene may have a different pathway of formation that probably does not involve enzymatic synthesis.
Keywords: monoterpene emission; monoterpene fumigation; photosynthesis; Quercus ilex; respiration; thermotolerance

Different sources of reduced carbon contribute to form three classes of terpenoid emitted by Quercus ilex L leaves - Loreto, F; Ciccioli, P; Brancaleoni, E; Cecinato, A; Frattoni, M; Sharkey, T D (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE UNITED STATES OF AMERICA, 1996)
Quercus ilex L. leaves emit terpenes but do not have specialized structures for terpene storage. We exploited this unique feature to investigate terpene biosynthesis in intact leaves of Q. ilex. Light induction allowed us to distinguish three classes of terpenes: (i) a rapidly induced class including alpha-pinene; (ii) a more slowly induced class, including cis-beta-ocimene; and (iii) the most slowly induced class, including 3-methyl-3-buten-1-ol. Using C-13, we found that alpha-pinene and cis-beta-ocimene were labeled quickly and almost completely while there was a delay before label appeared in linalool and 3-methyl-3-buten-1-ol. The acetyl group of 3-methyl-3-buten-1-yl acetate was labeled quickly but label was limited to 20% of the moiety. It is suggested that the ocimene class of monoterpenes is made from one or more terpenes of the alpha-pinene class and that both classes are made entirely from reduced carbon pools inside the chloroplasts. Linalool and 3-methyl-3-buten-1-ol are made from a different pool of reduced carbon, possibly in nonphotosynthetic plastids. The acetyl group of the 3-methyl-3-buten-1-yl acetate is derived mostly from carbon that does not participate in photosynthetic reactions. Low humidity and prolonged exposure to light favored ocimenes emission and induced linalool emission. This may indicate conversion between terpene classes.
APS
Keywords: acetyl group labelling; alpha-pinene; light induction; monotherpenes; Quercus ilex L.; terpenes biosynthesis

Evidence of the photosynthetic origin of monoterpenes emitted by Quercus ilex L leaves by C-13 labeling - Loreto, F; Ciccioli, P; Cecinato, A; Brancaleoni, E; Frattoni, M; Fabozzi, C; Tricoli, D (PLANT PHYSIOLOGY, 1996)
The carbon of the four main monoterpenes emitted by Quercus flex L. leaves was completely labeled with C-13 after a 20-min feeding with 99% (CO2)-C-13. This labeling time course is comparable with the labeling time course of isoprene, the terpenoid emitted by other Quercus species and synthesized in leaf chloroplasts. It is also comparable with that of phosphoglyceric acid. Our experiment therefore provides evidence that monoterpenes emitted by Q. ilex are formed from photosynthesis intermediates and may share the same synthetic pathway with isoprene. By analyzing the rate and the distribution of labeling in the different fragments, we looked for evidence of differential carbon labeling in the alpha-pinene emitted. However, the labeling pattern was quite uniform in the different fragments, suggesting that the carbon skeleton of the emitted monoterpenes comes from a unique carbon source.
APS
Keywords: alpha-pinene; C-13 labeling; Emissions; isoprene; Monoterpenes; Quercus flex L.; Quercus ilex

Influence of environmental factors and air composition on the emission of alpha-pinene from Quercus ilex leaves - Loreto, F; Ciccioli, P; Cecinato, A; Brancaleoni, E; Frattoni, M; Tricoli, D (PLANT PHYSIOLOGY, 1996)
We studied the emission of alpha-pinene from Quercos ilex leaves. Only the abaxial side of the hypostomatous Q. ilex leaf emits alpha-pinene. Light induced photosynthesis and alpha-pinene emission. However, the response of photosynthesis to dark-to-light transitions was faster than that of alpha-pinene, suggesting that ATP controls the emission. The emission was higher at 30 than at 20 degrees C, whereas photosynthesis did not change. Therefore, the relationship between photosynthesis and alpha-pinene emission does not always hold. When CO2 was removed from the air, transpiration was stimulated but photosynthesis and alpha-pinene emission were inhibited. alpha-Pinene inhibition was more rapid under low O-2. When CO2 in the air was increased, photosynthesis was stimulated and transpiration was reduced, but alpha-pinene emission was unaffected. Therefore, the emission depends on the availability of photosynthetic carbon, is not saturated at ambient CO2, and is not dependent on stomatal opening. The pattern of alpha-pinene emission from Q. ilex is different from that of plants having specialized structures for storage and emission of terpenes. We suggest that alpha-pinene emitted by Q. ilex leaves is synthesized in the chloroplasts and shares the same biochemical pathway with isoprene emitted by isoprene-emitting oak species.
APS
Keywords: alpha-pinene; photosynthesis; Quercus ilex